Investigating the existence of neural stem cells in the adult mouse cerebellum and third ventricle - Salih, Shelanah (2016)
In mammals, adult neurogenesis in the subventricular zone (SVZ) of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus produces neurons contribute to learning and memory functions. However, more recent evidence suggests that neurogenesis may also happen in other regions of the brain such as striatum, spinal cord, and hypothalamus (Reviewed in (Riddle, 2007)). It is important to determine if neurogenesis also occurs in non-neurogenic regions of the adult brain such as CB and 3V. This would be of importance for potential future therapeutic applications for brain repair, and also to help understand the fundamental function of the different regions of the adult brain.